Good Sleep Quality Improves the Relationship Between Pain and Depression Among Individuals With Chronic Pain - Zambelli, Zoe; Halstead, Elizabeth J.; Fidalgo, Antonio R.; Dimitriou, Dagmara (Frontiers in Psychology, 2021)
Individuals with chronic pain often experience co-existing sleep problems and depression-related states. Chronic pain, sleep problems, and depression interrelate, and have been shown to exacerbate one another, which negatively impacts quality of life. This study explored the relationships between pain severity, pain interference, sleep quality, and depression among individuals with chronic pain. Secondly, we tested whether sleep quality may moderate the relationship between pain and depression. A cross-sectional survey was completed by 1,059 adults with non-malignant chronic pain conditions (Mage 43 years, 88% identified as women) and collected measures related to pain severity, pain interference, sleep quality and depression. Multiple regression analyses found that pain severity, pain interference and sleep quality are all significantly associated with depression. Secondly, moderated regression analyses revealed that sleep quality moderates the relationship between pain interference and depression among individuals with chronic pain such that good sleep quality attenuates the effect of pain interference on depression, and poor sleep quality amplifies the effect of pain interference on depression. These findings suggest that sleep quality may be a relevant therapeutic target for individuals with chronic pain and co-existing depression.